Multi-trait discovery and fine-mapping of lipid loci in 125,000 individuals of African ancestry - Abram Bunya Kamiza; Sounkou M. Touré; Feng Zhou; Opeyemi Soremekun; Cheickna Cissé; Mamadou Wélé; Aboubacrine M. Touré; Oyekanmi Nashiru; Manuel Corpas; Moffat Nyirenda; Amelia Crampin; Jeffrey Shaffer; et al. (Nature Communications, 2023)
Abstract Most genome-wide association studies (GWAS) for lipid traits focus on the separate analysis of lipid traits. Moreover, there are limited GWASs evaluating the genetic variants associated with multiple lipid traits in African ancestry. To further identify and localize loci with pleiotropic effects on lipid traits, we conducted a genome-wide meta-analysis, multi-trait analysis of GWAS (MTAG), and multi-trait fine-mapping (flashfm) in 125,000 individuals of African ancestry. Our meta-analysis and MTAG identified four and 14 novel loci associated with lipid traits, respectively. flashfm yielded an 18% mean reduction in the 99% credible set size compared to single-trait fine-mapping with JAM. Moreover, we identified more genetic variants with a posterior probability of causality >0.9 with flashfm than with JAM. In conclusion, we identified additional novel loci associated with lipid traits, and flashfm reduced the 99% credible set size to identify causal genetic variants associated with multiple lipid traits in African ancestry.